A unique case of Schistosoma‐related ureteral stricture: Diagnosis and surgical reconstruction - Jonathan A Seaman; Erika Bracamonte; Sunchin Kim (IJU Case Reports, 2023)
Background Chronic infection with Schistosoma haematobium can lead to pathology of the upper and lower urinary tracts. While well known as a cause of squamous cell carcinoma of the bladder, relatively little research exists on ureteral involvement. Here, we present a unique case of bilateral ureteral obstruction from schistosomiasis with concomitant ureteral stone disease. Case presentation A 43‐year‐old male Somalian immigrant was diagnosed with a right proximal ureteral stone and bilateral multifocal ureteral narrowing causing obstruction with preserved renal function. He underwent a staged repair with right robotic pyelolithotomy and non‐transecting ureteroureterostomy, followed by left robotic ureteroureterostomy with stricture excision. Pathology revealed Schistosoma ova. Conclusion Ureteral stricture from schistosomiasis represents a rare diagnosis for urologists in non‐endemic countries. Bilateral ureteral narrowing and concomitant ureteral stone burden presented both diagnostic and reconstructive challenges, requiring a staged repair. Minimally invasive reconstruction was achieved using robotic assistance with good functional outcome.